2015
DOI: 10.1111/jerd.12157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bleaching Treatment on Fatigue Resistance and Flexural Strength of Bovine Dentin

Abstract: It remains prudent to advise patients to limit their exposure to tooth bleaching materials by avoiding direct application of bleach to exposed dentin and by minimizing the duration of bleach treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
2
0
3
Order By: Relevance
“…This study confirms the findings of a previous paper which reported an adverse effect on the same mechanical properties of bovine dentin after simulated night-time tray-bleaching [29]. There was a reduction in dentin flexural strength and fracture resistance when 10% carbamide peroxide was applied in a simulated tray-bleaching technique for a total time of 84 or 288 hours [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study confirms the findings of a previous paper which reported an adverse effect on the same mechanical properties of bovine dentin after simulated night-time tray-bleaching [29]. There was a reduction in dentin flexural strength and fracture resistance when 10% carbamide peroxide was applied in a simulated tray-bleaching technique for a total time of 84 or 288 hours [29].…”
Section: Discussionsupporting
confidence: 90%
“…Fatigue tests are more useful than strength tests to assess structural longevity [28]. A recent in vitro study reported a significant decrease in the fatigue resistance of bovine dentin following the use of a tray-delivered type of bleach application (10% carbamide peroxide, six hours a day for 2- or 8-weeks) [29]. In comparison to a tray-delivered type of bleach application, whitening strips generally utilize a hydrogen peroxide formulation rather than a carbamide peroxide formulation, a higher concentration of bleach, a smaller volume of bleach, a shorter bleach application time, and a thin polymer strip rather than a full contour tray.…”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se que, como a dentina e o esmalte são estruturas permeáveis ou semi--permeáveis, o peróxido de hidrogênio seja capaz de difundir-se livremente por meio dessas estruturas e alterações na superfície do esmalte dental possam ocorrer 16,18 . Entretanto, os estudos disponíveis ainda não elucidaram de maneira clara quais os fatores que durante o clareamento podem inferir nas alterações morfológicas em esmalte dental e de que forma eles atuam para provocar variadas manifestações [19][20] .…”
Section: Discussionunclassified
“…A literatura já evidenciou que os agentes clareadores são capazes de afetar de forma similar tanto as superfícies dentárias humanas quanto as bovinas. Dessa forma, dentes bovinos podem substituir eficazmente os dentes humanos nas pesquisas odontológicas sendo o seu uso seguro independente das técnicas e materiais clareadores utilizados 16,21 . No estudo de Lia Mondelli et al 2 (2015), ao avaliar a microdureza em esmaltes bovinos após o clareamento, os autores puderam constatar que apenas em um grupo de amostra não havia acontecido alterações nas primeiras 24 horas.…”
Section: Discussionunclassified
See 1 more Smart Citation